2016
DOI: 10.1371/journal.pone.0165775
|View full text |Cite
|
Sign up to set email alerts
|

The Morphogenesis of Cranial Sutures in Zebrafish

Abstract: Using morphological, histological, and TEM analyses of the cranium, we provide a detailed description of bone and suture growth in zebrafish. Based on expression patterns and localization, we identified osteoblasts at different degrees of maturation. Our data confirm that, unlike in humans, zebrafish cranial sutures maintain lifelong patency to sustain skull growth. The cranial vault develops in a coordinated manner resulting in a structure that protects the brain. The zebrafish cranial roof parallels that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 69 publications
4
48
0
Order By: Relevance
“…In the wild type, fgfr3 appeared to the fgfr gene most strongly expressed by osteoblasts and chondrogenic cells ( Figure 7A-C); this observation was in line with the literature data (Ledwon et al, 2018;Topczewska et al, 2016). fgfr3 was expressed in 40% of the OP5 late osteoprogenitors and in 75% of the osteoblasts.…”
Section: Fgfr3 Is Expressed By Late Osteoprogenitors Through To Matursupporting
confidence: 90%
See 3 more Smart Citations
“…In the wild type, fgfr3 appeared to the fgfr gene most strongly expressed by osteoblasts and chondrogenic cells ( Figure 7A-C); this observation was in line with the literature data (Ledwon et al, 2018;Topczewska et al, 2016). fgfr3 was expressed in 40% of the OP5 late osteoprogenitors and in 75% of the osteoblasts.…”
Section: Fgfr3 Is Expressed By Late Osteoprogenitors Through To Matursupporting
confidence: 90%
“…On the fertile side of the sutures, FGFR3 is expressed less strongly than FGFR2 and FGFR1 (Delezoide et al, 1998). In the zebrafish, previous studies and our present single-cell transcriptomic analysis revealed that expression levels of fgfr3 are higher than those of fgfr1a, fgfr1b and fgfr2 in (i) late osteoprogenitors and osteoblasts during cranial vault development and (ii) the osteogenic cells lining the suture's mineralization front (Topczewska et al, 2016). The situation is different in the rodent; Fgfr3c is almost completely absent from developing cranial bones, and is more weakly expressed than Fgfr2c and Fgfr1c in osteogenic fronts and sutures (Molténi et al, 1999;Rice et al, 2003).…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Less is known, however, about how potential defects in the embryonic progenitors that grow the skull bones may prefigure suture loss, although a few reports describe altered bone formation during embryonic stages in craniosynostosis mutants ( Merrill et al, 2006 ). The ex utero development and transparency of zebrafish provide a unique opportunity to track the progenitors that form the skull bones, and to better understand how defects in the dynamics of bone growth relate to a later ability to form and maintain sutures once the bones come together ( Quarto and Longaker, 2005 ; Laue et al, 2011 ; Kague et al, 2016 ; Topczewska et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%